2021
DOI: 10.1001/jama.2020.21465
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and Death After Initial Hospital Discharge Among Patients With COVID-19 in a Large Multihospital System

Abstract: Although more patients are surviving severe coronavirus disease 2019 (COVID-19), there are limited data on outcomes after initial hospitalization. We therefore measured the rate of readmission, reasons for readmission, and rate of death after hospital discharge among patients with COVID-19 in the nationwide Veterans Affairs (VA) health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
222
6
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(269 citation statements)
references
References 3 publications
32
222
6
9
Order By: Relevance
“…In a more recent study of 1,775 US veterans hospitalised with COVID-19, 20% were readmitted and 9% died within 60 days of discharge;[22] after restricting follow-up time in our study to the same duration, we found similar prevalence rates of 23% and 9%, respectively. The US study did not analyse organ-specific endpoints and was conducted in a specific population; we can thus now add that COVID-19 is associated with post-discharge manifestations in a range of organs in the general population.…”
Section: Discussionsupporting
confidence: 70%
“…In a more recent study of 1,775 US veterans hospitalised with COVID-19, 20% were readmitted and 9% died within 60 days of discharge;[22] after restricting follow-up time in our study to the same duration, we found similar prevalence rates of 23% and 9%, respectively. The US study did not analyse organ-specific endpoints and was conducted in a specific population; we can thus now add that COVID-19 is associated with post-discharge manifestations in a range of organs in the general population.…”
Section: Discussionsupporting
confidence: 70%
“…In a recent study of 1775 veterans in the United States admitted to hospital with covid-19, 20% were readmitted and 9% died within 60 days of discharge 25. After restricting follow-up in our study to the same length of time, we found similar prevalence rates of 23% and 9%, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…[5,6,[9][10][11] A few studies so far have described the utilisation of healthcare services after COVID-19, in particular hospitalisation. [7,8,[31][32][33] At two months, 9% to 20% of patients admitted for COVID-19 were found to require rehospitalisation, with a higher risk in individuals with comorbidities and older age. [7,8,[31][32][33] The observed rehospitalisation rate of about 10% in our study is broadly consistent with these estimates.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…[7,8,[31][32][33] At two months, 9% to 20% of patients admitted for COVID-19 were found to require rehospitalisation, with a higher risk in individuals with comorbidities and older age. [7,8,[31][32][33] The observed rehospitalisation rate of about 10% in our study is broadly consistent with these estimates. Chopra et al further reported that 78% of participants hospitalised for COVID-19 had seen a primary care physician after hospital discharge.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation